201k views
4 votes
Simplify: (3x+3) (x + 2)

User Bsegraves
by
5.1k points

2 Answers

5 votes

Answer:
3x^(2) + 9x + 6

Step-by-step explanation:

(3x + 3) (x + 2) Apply the distributive property twice to solve

3x(x + 2) = 3x^2 + 6x

3( x + 2) = 3x + 6

Now put them together to combine like terms


3x^(2) + 6x + 3x + 6


3x^(2) + 9x + 6

User Serginho
by
4.6k points
1 vote

Answer:

3x² + 9x + 6

Step-by-step explanation:

(3x + 3)(x + 2)

= (3x + 3)(x + 2)

= (3x)(x) + (3x)(2) + (3)(x) + (3)(2)

= 3x² + 6x + 3x + 6

= 3x² + 9x + 6

User Andrej Herich
by
5.4k points